Money monster [videorecording (DVD)] - Clooney, George; Roberts, Julia, 1967-; O'Connell, Jack, 1989- (Sony Pictures Home Entertainment, 2016)
In the real-time high stakes thriller, financial TV host Lee Gates and his producer Patty, are put in an extreme situation when an irate investor who has lost everything forcefully takes over their studio. During a tense standoff broadcast to millions on live TV, Lee and Patty must work furiously against the clock to unravel the mystery behind a conspiracy at the heart of today's fast-paced, high-tech global markets.